“It’s because they’re my kids, and I love them”: Substance use disorders’ impact on children and families: A secondary analysis - Meghan K. Ford; Ryan Truong; Ayesha Shakeel; Bruce Knox; Susan Bartels; Colleen Davison; Michele Cole; Logan Jackson; Eva Purkey; Imaan Bayoumi (PLoS ONE, 2025)
Background Substance use disorders (SUD) significantly impact the physical, social, and mental health of individuals, their families, and the wider community. Parental substance use can lead to long-term social and health problems for children. Examining resilience and its determinants among families directly affected by may uncover valuable insights to support families addressing SUD. The existing literature does not adequately address substance use within the context of families with young children and community resilience. Aim The current study aims to enhance our understanding of the daily impact of family members’ direct substance use or exposure to indirect substance use within the community on children and families through qualitative interviews. Methods The present study was a qualitative secondary analysis. Families with a self-identified history of adversity and resilience were enrolled in the main study. The qualitative transcripts were analyzed following reflexive thematic analysis. Findings Six families (12 adults, 4 children) were included in the secondary analysis. The analysis generated four themes: (1) How children affect resilience in families affected by SUD; (2) Service needs of parents with SUD to enhance family resilience; (3) The role of social support in family resilience; and (4) How perceptions of safety and trust challenge community resilience. Conclusions The study highlights the significant impact of family and community on the resilience of individuals affected by SUD. It emphasizes the importance of developing addictions services and social environments that are supportive of families with young children and supports the need for services that are substance-free, inclusive, and welcoming to children. Additionally, there is a need to improve service navigation and reduce barriers to care commonly experienced by parents affected by SUD.